Improvement of Hole Erosion Test and Results on Reference Soils - Haghighi, Iman; Chevalier, Christophe; Duc, Myriam; Guédon, Sylvine; Reiffsteck, Philippe (Journal of geotechnical and geoenvironmental engineering, 2013)
AbstractUnderstanding the factors that control the transport of soil particles detached by water is essential in predicting the contingency of internal and surface erosion of embankments during storms and floods. It is particularly useful to be able to evaluate the sensitivity of the available soils to erosion at an early stage of a project and the risk assessment of an existing earthwork. The presented study is based on laboratory tests with a hole erosion test apparatus and tries to characterize the internal erosion of soils. The test consists of eroding a drilled soil specimen by water flow with a constant pressure drop at the boundaries of the specimen while recording the flow rate and studying the hole enlargement. A new version of the apparatus with improved instruments and an interpretation method is proposed, estimating the erosion rate based on the turbidity of the outflow and independent of hydraulic charge. Several remolded kaolinite-sand mixtures are tested as reference soil textures, and the results are analyzed with the proposed and existing interpretation methods.